Rotation symmetry mismatch and interlayer hybridization in MoS2-black phosphorus van der Waals heterostructures - Zailan Zhang; Alberto Zobelli; Chaofeng Gao; Yingchun Cheng; Jiuxiang Zhang; Jonathan Caillaux; Lipeng Qiu; Songlin Li; Mattia Cattelan; Viktor Kandyba; Alexei Barinov; Mustapha Zaghrioui; et al. (Nature Communications)
Abstract Interlayer coupling in 2D heterostructures can result in a reduction of the rotation symmetry and the generation of quantum phenomena. Although these effects have been demonstrated in transition metal dichalcogenides (TMDs) with mismatched interfaces, the role of band hybridization remains unclear. In addition, the creation of flat bands at the valence band maximum (VBM) of TMDs is still an open challenge. In this work, we investigate the electronic structure of monolayer MoS2-black phosphorus heterojunctions with a combined experimental and theoretical approach. The disruption of the rotational symmetry of the MoS2 bands, the creation of anisotropic minigaps and the appearance of flat bands at the Γ valley, accompanied by the switch of VBM from K to Γ, are clearly observed with micro-ARPES. Unfolded band structures obtained from first principles simulations precisely describe these multiple effects – all independent of the twist angle – and demonstrates that they arise from strong band hybridization between Mo $${d}_{{z}^{2}}$$ d z 2 and P $${p}_{x}$$ p x orbitals. The underlying physics revealed by our results paves the way for innovative electronics and optoelectronics based on TMDs superlattices, adding further flexibility to the approaches adopted in twisted hexagonal superlattices.